2019
DOI: 10.1016/j.clinthera.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High-cost Patients With Noninfectious Inflammatory Eye Diseases

Abstract: Purpose: Noninfectious inflammatory eye diseases (NIIEDs), such as uveitis, is a general term used to describe a complex mix of acute, chronic, allergic, and inflammatory disorders. Prior literature has established that, in addition to severe clinical burden, NIIEDs is associated with significant economic burden for US payers; however, no literature provides a current estimate of the economic burden associated with patients with high-cost NIIEDs. This study aimed to better understand the cost and resource use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
1
9
0
4
Order By: Relevance
“…These groups include all patients with significant economic and clinical burdens. Consistent with our analyses, other scholars have found that hospitalization accounted for almost all total spending among HC patients ( Meyers et al, 2014 ; Rice et al, 2017 ; Nelson et al, 2019 ). Almost all of our HC patients were hospitalized at least once during 12-month follow-up, whereas Meyers and colleagues showed a lower (but explainable) figure because our study population was aged >65 years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These groups include all patients with significant economic and clinical burdens. Consistent with our analyses, other scholars have found that hospitalization accounted for almost all total spending among HC patients ( Meyers et al, 2014 ; Rice et al, 2017 ; Nelson et al, 2019 ). Almost all of our HC patients were hospitalized at least once during 12-month follow-up, whereas Meyers and colleagues showed a lower (but explainable) figure because our study population was aged >65 years.…”
Section: Discussionsupporting
confidence: 92%
“…Another concordant comorbidity more likely to be recorded in T2DM patients was hyperuricemia/gout (OR 2.49,95% CI,. As reported recently, there appears to be a three-way association between hyperuricemia, T2DM, and hypertension (Mortada, 2017). Moreover, hyperuricemia has emerged as an independent risk factor in T2DM development and hypertension through several postulated mechanisms (Kuwabara et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Causa el 10-15 % de la ceguera mundial 1,2,5 y es la tercera causa de ceguera prevenible en el mundo. 6 Adicionalmente, el 25-50 % de los pacientes tendrán una enfermedad sistémica asociada. 2 Existen cuestionarios de calidad de vida relacionada con la visión y han encontrado que la función visual y el estado de general de salud es peor que en las personas sanas.…”
Section: Introductionunclassified
“…8 Al presentarse en edades productivas causa un impacto socioeconómico importante. 6 Este depende de múltiples factores, como la causa y duración de la enfermedad, comorbilidades, el ingreso del paciente/ familia o el apoyo gubernamental. 2 Hasta ahora carecemos de información sobre el efecto psicosocial y económico que experimentan los pacientes diagnosticados con uveítis en México.…”
Section: Introductionunclassified